2021
DOI: 10.1515/biol-2021-0062
|View full text |Cite
|
Sign up to set email alerts
|

T cell epitopes of SARS-CoV-2 spike protein and conserved surface protein of Plasmodium malariae share sequence homology

Abstract: Since its emergence in late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been spreading remarkably fast worldwide. Effective countermeasures require the rapid development of data and tools to monitor its spread and better understand immunogenic profile. However, limited information is available about the tools and target of the immune responses to SARS-CoV-2. In this study, we excogitated a new approach for analyzing phylogenetic relationships by using the whole prototype proteome seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…These data suggest the third possibility by which the T-cells, recognizing the epitopes, are primed by the exposure to other ubiquitous antigens. A recent report suggested that such sequence homology exists between SARS-CoV-2 peptides and peptides from allergen proteins [71], malaria proteins [72], and antigenic proteins in BCG, OPV, MMR, and some other vaccines [73]. Perhaps sequence homology, in the context of 9-mer T-cell epitopes, between pathogens is more common than what was originally thought.…”
Section: Epitope Cross-reactivity With Human Peptides Human Common Co...mentioning
confidence: 99%
“…These data suggest the third possibility by which the T-cells, recognizing the epitopes, are primed by the exposure to other ubiquitous antigens. A recent report suggested that such sequence homology exists between SARS-CoV-2 peptides and peptides from allergen proteins [71], malaria proteins [72], and antigenic proteins in BCG, OPV, MMR, and some other vaccines [73]. Perhaps sequence homology, in the context of 9-mer T-cell epitopes, between pathogens is more common than what was originally thought.…”
Section: Epitope Cross-reactivity With Human Peptides Human Common Co...mentioning
confidence: 99%
“…For analysis of anti-NP antibody kinetics, samples were drawn serially from 72 SARS-CoV-2 RT-PCR-confirmed patients. Overall, patients were followed for a median of 31 [interquartile range (IQR): [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] days, and ranging between 7 to 37 days. Whenever possible, samples were drawn every 3 days during follow-up.…”
Section: Data and Specimen Collectionmentioning
confidence: 99%
“…Antibody testing for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is used for epidemiological surveillance, in aiding the diagnosis of (previous) coronavirus disease 2019 (COVID- 19), and in the assessment of herd immunity following natural infection or after vaccine administration [1][2][3][4][5][6][7][8][9]. Several reports have demonstrated a lack of specificity for SARS-CoV-2 antibodies in evaluations of samples both pre-pandemic as well as samples collected during the COVID-19 pandemic period [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon the database search, these 7 amino acids motif was found to share 100% similarity with P. malariae conserved membrane bound-surface protein. Performing a CD4 T-cell epitope analysis resulted in two epitopes with the core peptide motif (NNLDSKV) that have 97.72 and 98.60% immunogenicity and bind MHC-I alleles (HLA-A*24:02, HLA-A*02:01 and other alleles) ( 107 , 108 ). While the preparation of this review was underway an international group headed by Prof. Bei, Yale University demonstrated that antibodies generated against malaria would interact with SARS-CoV-2 surface protein.…”
Section: Bioinformatics Similarities Between Malaria and Covid-19mentioning
confidence: 99%